2023
DOI: 10.1177/11782218231166622
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review of Risk and Protective Factors for Negative Cannabis Use Consequences

Abstract: Objective: Numerous reviews have examined risk and protective factors for alcohol-related negative consequences, but no equivalent review of risk and protective factors exists for cannabis-related negative consequences (CRNCs)-a gap filled by the present study. This scoping review examined survey-based research of risk and protective factors for CRNCs such as neglecting responsibilities, blacking out, or needing more cannabis. Methods: Three databases (PubMed, PsycINFO, and Google Scholar) were searched for pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 132 publications
(209 reference statements)
0
1
0
Order By: Relevance
“…However, our results showed that, in all the included studies, cannabis-related negative consequences and change in behavior (CU frequency) were measured at the same time point, namely, 3 months after the baseline. Moreover, Grigsby et al [ 124 ] conducted a scoping review of risk and protective factors for CU and suggested that interventions to reduce negative CU consequences should prioritize multilevel methods or strategies “to attenuate the cumulative risk from a combination of psychological, contextual, and social influences.”…”
Section: Discussionmentioning
confidence: 99%
“…However, our results showed that, in all the included studies, cannabis-related negative consequences and change in behavior (CU frequency) were measured at the same time point, namely, 3 months after the baseline. Moreover, Grigsby et al [ 124 ] conducted a scoping review of risk and protective factors for CU and suggested that interventions to reduce negative CU consequences should prioritize multilevel methods or strategies “to attenuate the cumulative risk from a combination of psychological, contextual, and social influences.”…”
Section: Discussionmentioning
confidence: 99%